2019
DOI: 10.1038/s41598-019-46084-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased sub-clinical levels of autistic traits are associated with reduced multisensory integration of audiovisual speech

Abstract: Recent studies suggest that sub-clinical levels of autistic symptoms may be related to reduced processing of artificial audiovisual stimuli. It is unclear whether these findings extent to more natural stimuli such as audiovisual speech. The current study examined the relationship between autistic traits measured by the Autism spectrum Quotient and audiovisual speech processing in a large non-clinical population using a battery of experimental tasks assessing audiovisual perceptual binding, visual enhancement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 64 publications
4
19
0
Order By: Relevance
“…This result argues against a deterministic view of individual differences in the McGurk effect. A growing body of literature shows that McGurk susceptibility is significantly, but weakly, correlated with a number of cognitive and personality factors, including the pattern of eye movements made when viewing a talking face (Gurler et al, 2015); lipreading skill (Strand et al, 2014; Brown et al, 2018); temporal binding window (Stevenson et al, 2012); and autistic traits (Van Laarhoven et al, 2019). Taken together, these findings suggest that audiovisual speech perception, as assayed with the McGurk effect, is similar to other complex human behaviors in that it is influenced by a host of factors, both genetic and environmental.…”
Section: Discussionmentioning
confidence: 99%
“…This result argues against a deterministic view of individual differences in the McGurk effect. A growing body of literature shows that McGurk susceptibility is significantly, but weakly, correlated with a number of cognitive and personality factors, including the pattern of eye movements made when viewing a talking face (Gurler et al, 2015); lipreading skill (Strand et al, 2014; Brown et al, 2018); temporal binding window (Stevenson et al, 2012); and autistic traits (Van Laarhoven et al, 2019). Taken together, these findings suggest that audiovisual speech perception, as assayed with the McGurk effect, is similar to other complex human behaviors in that it is influenced by a host of factors, both genetic and environmental.…”
Section: Discussionmentioning
confidence: 99%
“…Another two studies, however, did find significant correlations between increased autistic traits and altered audiovisual temporal processing. These two studies separated autistic traits into several dimensions and found that different dimensions of autistic traits were differentially correlated with the width of the TBW [van Laarhoven et al, 2019; Yaguchi & Hidaka, 2018]. The above findings indicate the necessity to more carefully examine how multidimensional autistic symptoms are involved in multisensory integration.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with elevated autistic traits seem to have normal width of TBW compared with their low‐trait counterparts [Donohue, Darling, & Mitroff, 2012; Noel, Lytle, Cascio, & Wallace, 2018; Zhou, Shi, Yang, Cheung, & Chan, 2020]. This lack of significant correlation between autistic traits and audiovisual TBW may be partly due to the fact that autistic traits comprise various dimensions that are differentially and oppositely correlated with the width of audiovisual TBW [van Laarhoven, Stekelenburg, & Vroomen, 2019; Yaguchi & Hidaka, 2018]. Specifically, autistic traits of social skills and attention to detail were found to be associated with a narrower TBW, whereas autistic traits of communication and attention switching were correlated with a wider TBW [van Laarhoven et al, 2019; Yaguchi & Hidaka, 2018].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility to the McGurk effect is decreased in autistic individuals compared to typically developed (TD) individuals (e.g., de Gelder et al, 1991;Iarocci et al, 2010;Saalasti et al, 2012;van Laarhoven et al, 2019;Williams et al, 2004). Autistic individuals are likely to be diagnosed with autism spectrum disorder (ASD), which is a neurodevelopmental disorder characterized by difficulties with social interaction and communication, patterns of repetitive behavior, narrow interests, and difficulties with sensory processing ; American Psychiatric Association, 2013].…”
Section: A Weaker Mcgurk Effect In Autism Spectrum Disordermentioning
confidence: 99%